Effect of incorporation of crop residues on a maize-groundnut sequence in the humid tropics. I. Yield and nutrient uptake - Mubarak, A.R.; Rosenani, A.B.; Anuar, A.R.; Siti Zauyah, D. (Marcel Dekker, 2002)
Low soil organic matter (OM) characterizes most soils of the humid tropics because crop residues are not returned to the field. A two-year (1997-1999) field experiment was carried out in an Ultisol to determine the contribution of crop residue application in sustaining yields of maize (Zea mays L.) and groundnut (Arachis hypogaea) in a crop rotation system. Three management practices were compared, inorganic fertilizer with crop residues (T1), inorganic fertilizer without crop residue (T2) and half dose of inorganic fertilizer with crop residues combined with chicken manure (CM) (T3), in a randomized block design. During five crops cycle of continuous application of crop residues with inorganic fertilizers or combined with CM, 43% of the observed maximum yield of the maize was sustained compared to 21% in plots where crop residues were removed. Nitrogen (N) and potassium (K) uptake by the subsequent crops were significantly higher in crop residue treatments whereas phosphorus (P), calcium (Ca), and magnesium (Mg) were not significantly affected by application of crop residues. In the highly weathered soils of the tropics, incorporation of crop residues appeared to be a beneficial management practice for sustaining crop yields.